Perancangan Enterprise Architecture Media Informasi Dinas Kebakaran dan Penanggulangan Bencana Kota Bandung : Indonesia - sofia dewi; Muhammad Prakarsa A.S; Siti Fatimah (Jurnal Accounting Information System (AIMS), 2022)
In the use of information technology in an organization, it is very necessary, especially for large organizations such as the Fire and Disaster Management Agency (DKPB). Guidelines for the Management of Information and Documentation Services in the Bandung City Government that are currently running have not utilized technology in the process of activities carried out by the DKPB. In practice, not a few information system developments fail, this is because they are not in accordance with the direction of goals and needs such as information systems should be built without referring to the provisions contained in Bandung Mayor Regulation No. 1340 of 2017 concerning public information. One of them is the use of internet technology as a medium of information. The purpose of this research is to provide input on the benefits of developing an architecture that can participate in advancing the management of information and documentation services at DKPB. Enterprise architecture planning is modeling the system using the Unified Modeling Language (UML). The result of this design is a web-based application that provides information on official profiles, news, report galleries, services or contact us. It is hoped that this application can become one of the websites of the Fire and Disaster Management Service which can also be used by the public/users. The provision of web-based DKPB information will make it easier to obtain information and provide reports on current events. It is hoped that the public can use information media to obtain the required DKPB information.